慢性透析患者におけるりんの血中動態 りんの赤血球膜透過と｀３１´ｐ ＮＭＲスペクトルの解析 - ONOHARA M.; KUNITOMO T.; NISHIUM S.; INAGAKI F.; SUGISAKI H. (Jinko Zoki, 1984)
To elucidate behaviors of phosphorus compounds including inorganic phosphate (Pi) which may be closely linked with bone metabolism, efflux of Pi from and 31P NMR spectra of RBC were measured. Efflux of Pi from RBC into dialyzed plasma or saline lasts even after outer Pi concentration exceeds the original plasma Pi level, which suggests the Pi transport not controlled only by simple diffusion and the existence of Pi precursor (s) in RBC. 31P NMR spectra of RBC from dialysis patients reveal that it contains ATP and maybe sugar phosphate (SP) more than that from normal subjects and that 2, 3-diphosphoglycerate and SP are main precursors of Pi efflux from RBC. 尿素やクレアチニンとは違った特異的な血中無機リン酸(Pi)の透析中の動きを見い出したので, 骨代謝に関係の深いPiの体内動態をより詳しく調べるため, 細胞モデルとしての赤血球の膜を介してのPiの移動および31P NMR分析による赤血球内の各種リン化合物の動態を観察した。1)透析によって溶質を除去した血漿や人工生理溶液としての生食水中への赤血球からのPiの溶出は緩慢であるが, もともとその赤血球と平衡状態にあった血漿中の溶質濃度レベルを越えても溶出が続く。この現象は単純拡散では説明できず, また赤血球内におけるPiのprecursor(s)の存在を示唆する。2)透析患者赤血球中には高レベルのATPと, sugar phosphate(SP)と思われる物質の蓄積がみられる。インキュベーション法によって, 赤血球内のPiの主なprecursor(s)は2, 3-diphosphoglycerateとSPであると推定できる。